Pembelajaran Keaksaraan Awal Anak Usia 5–6 Tahun Melalui Pengembangan Media Pak Tua - Vania Febriyani, Elsa; Imani Khan, Rosa; Prastihastari Wijaya, Intan; Vania Febriyani, Elsa Vania Febriyani (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to determine the development of PAK TUA Media(Preliminary Reading Card Board) for early literacy learning for children aged 5-6years. This research refers to the type of development research. The developmentprocedure used refers to Borg and Gall's research and development procedures. Inthis study, simplification was carried out into 4 (four) stages (potential and problems,data collection, product design and product validation). The research instrument usedis an assessment questionnaire that will be filled out by material experts and mediaexperts. The data analysis uses the Aiken formula to determine the feasibility andattractiveness of the developed product in the form of PAK TUA Media. This studyconcludes that PAK TUA media is suitable for use as a medium for early literacylearning for children aged 5-6 years